A metabolomic platform to identify and quantify polyphenols in coffee and related species using liquid chromatography mass spectrometry - Castro-Moretti, Fernanda R.; Cocuron, Jean-Christophe; Castillo-Gonzalez, Humberto; Escudero-Leyva, Efrain; Chaverri, Priscila; Guerreiro-Filho, Oliveiro; Slot, Jason C.; Alonso, Ana Paula (Frontiers in Plant Science, 2023)
Products of plant secondary metabolism, such as phenolic compounds, flavonoids, alkaloids, and hormones, play an important role in plant growth, development, stress resistance. The plant family Rubiaceae is extremely diverse and abundant in Central America and contains several economically important genera, e.g. Coffea and other medicinal plants. These are known for the production of bioactive polyphenols (e.g. caffeine and quinine), which have had major impacts on human society. The overall goal of this study was to develop a high-throughput workflow to identify and quantify plant polyphenols. First, a method was optimized to extract over 40 families of phytochemicals. Then, a high-throughput metabolomic platform has been developed to identify and quantify 184 polyphenols in 15 min. The current metabolomics study of secondary metabolites was conducted on leaves from one commercial coffee variety and two wild species that also belong to the Rubiaceae family. Global profiling was performed using liquid chromatography high-resolution time-of-flight mass spectrometry. Features whose abundance was significantly different between coffee species were discriminated using statistical analysis and annotated using spectral databases. The identified features were validated by commercially available standards using our newly developed liquid chromatography tandem mass spectrometry method. For instance, caffeine, trigonelline and theobromine were highly abundant in coffee leaves, as expected. Interestingly, defense-related molecules, such as phenylpropanoids (e.g., cinnamic acid), the terpenoid gibberellic acid, and the monolignol sinapaldehyde were found more abundantly in wild Rubiaceae leaves.